The Influence of Brand Image, Price, and Promotion on Purchase Decisions of Teh Botol Sosro - Nathanael Napitupulu, S. Kristian; Kartika, Dewi; Lestari, Ade Nadia; Efendi, Nasrul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of brand image, price, and promotion on consumers' purchase decisions for Teh Botol Sosro in Medan. A quantitative descriptive approach was employed using data from 96 respondents selected through incidental sampling. The data were analyzed using multiple linear regression. The results indicate that promotion has a positive and significant effect on purchase decisions, whereas brand image and price have positive but insignificant effects. Simultaneously, all three variables significantly influence purchase decisions, explaining 64.2% of the variance. These findings suggest that strengthening promotional strategies while maintaining brand consistency and competitive pricing can improve consumer purchase decisions.